Chemokine ligand 20 (CCL20) expression increases with NAFLD stage and hepatic stellate cell activation and is regulated by miR-590-5p. (November 2019) - Hanson, Amanda; Piras, Ignazio S.; Wilhelmsen, Danielle; Still, Christopher D.; Chu, Xin; Petrick, Anthony; Gerhard, Glenn S.; DiStefano, Johanna K.
Abstract: CCL20 (CC chemokine ligand 20) is emerging as an important regulatory molecule in a pathway common to virus infection, alcoholic hepatitis, and non-alcoholic fatty liver disease (NAFLD) leading to the development of hepatic fibrosis. We previously observed upregulation of CCL20 in patients with NAFLD fibrosis and human hepatic stellate cells (LX-2 cells) in response to lipid loading. To date, the mechanisms mediating the relationship between CCL20 and hepatic fibrogenesis remain unknown. In this study, we sought to characterize the molecular mechanisms by which CCL20 may contribute to fibrogenesis in NAFLD. We observed that CCL20 levels increased with worsening severity of liver histology in NAFLD patients (normal < steatosis < inflammation < fibrosis) and during LX-2 cell activation in a time-dependent manner. We found that treatment of LX-2 cells with CCL20 corresponded with increased levels of CCL20 and ACTA2, and decreased levels of PLAU and SERPINE1, effects mitigated by CCL20 knockdown. We identified a putative binding site for miR-590-5p, which we previously reported to be downregulated in NAFLD fibrosis, in the CCL20 3′ untranslated region (3′UTR), and found that exogenous miR-590-5p functionally interacted with the CCL20 3′UTR to downregulate its expression. Transfection of LX-2 hepatic stellate cells with miR-590-5p mimic or silencing RNA resulted in decreased or increased CCL20 levels, respectively. Our results indicate an association between CCL20 and hepatic stellate cell activation that includes modulation of key ECM components and functional interactions with a miRNA previously implicated in NAFLD fibrosis. Together, these findings support a novel mechanism by which CCL20 may promote fibrogenesis in NAFLD.